Assessing Groundwater Quality for Agricultural Applications in Bemban, Melaka: Implications for Sustainable Farming Practices - IKHWAT, MOHAMAD AZWAN; SALLEH, SHAHRUN NAZIDA (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2023)
Groundwater's significance in safeguarding food security becomes even more critical, particularly amidst the unpredictability of climate change. The utilization of groundwater in Bemban remains significantly underutilized, despite the fact that the local villagers engage in small-scale agricultural practices with a focus on sustainable productivity. Several agriculture practitioners rely on river water for irrigation purposes; however, the combination of a hot climate and limited water availability adversely affects crop growth, leading to stunted plants and diminished agricultural yields. This research aims to evaluate the groundwater and river water quality in comparison to guidelines from the National Water Quality Index Classification and Water Quality Interpretation Guidelines for Irrigation in Bemban, Melaka. Two groundwater sampling wells along with a nearby river were utilized to collect representative samples, which were subsequently analyzed for various key characteristics include pH, ammoniacal nitrogen (AN), total suspended solids (TSS), chemical oxygen demand (COD), dissolve oxygen (DO), biochemical oxygen demand (BOD), electrical conductivity (EC), total dissolved solids (TDS), and turbidity. The test results were compared with the guidelines provided by the National Water Quality Index Classification (NWQS) and Water Quality Interpretation Guidelines for Irrigation. The results show the parameter pH and COD are within the acceptable tolerance range, indicating that The water is able to be used for irrigation. The research findings will play a crucial role in persuading agriculture practices to utilize their well water for irrigation purposes. This will contribute to enhancing the overall efficiency and sustainability of agricultural practices in the region. Further investigations should focus on finding the parameters for Groundwater Quality Index (GWQI) for Bemban’s agriculture landscape